Antifungal Properties of Palepek Baringin Wood (Shorea leavis Ridl) - Renhart Jemi; Wasrin Syafii; Fauzi Febrianto; Muhammad Hanafi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2012)
The objectives of this research were to evaluate the extractive substances of heartwood of palepek baringin wood (Shorea leavis Ridl) as a bio-active substance to wood destroying fungi i.e. Schizophyllum commune Fr and Pleurotus ostreatus. The 40 mesh of heartwood meals was extracted by methanol, chloroform, ethyl acetate, n-hexane and buthanol. The extractives obtained were subjected to wood destroying fungi S. commune and P. ostreatus, and preservative containing copper, chrome and boron (CCB) was used for comparison. The extractive of palepek baringin wood was dominated by ethylacetate fraction (3.54%), followed by chloroform and butanol fraction 1.73% and n-hexane (0.09%). All fractions have an antifungal activity to inhibit the growth of S. commune and P. ostreatus. Concentration of 50 ppm butanol fraction inhibited the growth of S. commune, and concentration of 250 ppm chloroform fraction inhited the growth of Pleurotus sp. Preservative of CCB 100 ppm inhibited the growth of S. commune and P. ostreatus by 43%. Butanol fraction contained 16 active compounds (PB.1-PB.16) that could inhibit the growth both of S. commune and P. ostreatus with IC50 54.29-64.32 and 48.40-65.86 ppm, respectively. Based on mass spectrometry (LC-MS) and 1HNMR analysis, the compound of PB.1.1 which has anti-fungal activity was 2,3-dihydroxyoctadecanoic acid.Key words: 2,3-dihydroxyoctadecanoic acid, antifungal, Pleurotus ostreatus, Schyzophlum commune, Shorea leavis